Positive basophil activation test with soymilk protein identifies Gly m 4–related soymilk allergy. Issue 5 (7th May 2021) - Yoshida, Tokiko; Chinuki, Yuko; Matsuki, Shingo; Morita, Eishin
Abstract: Soymilk allergy is caused by cross‐reaction of either birch Bet v 1–specific or alder Aln g 1–specific IgE to soybean Gly m 4, which belongs to pathogenesis‐related protein‐10 (PR‐10) family. Gly m 4–specific IgE test identifies soybean allergy patients with high sensitivity. In this case study, we found that CD203c expression–based basophil activation test (CD203c‐BAT) with soymilk protein became positive in the three cases of Gly m 4–related soymilk allergy at the concentrated of 1 μg/ml, but not in the control subjects. CD203c‐BAT may possibly be useful as a diagnostic tool to identify patients with soymilk allergy.